2007
DOI: 10.1016/j.bone.2007.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of spaceflight-induced bone loss: Bone mineral density after long-duration missions as fitted with an exponential function

Abstract: The loss of bone mineral in NASA astronauts during spaceflight has been investigated throughout the more than 40 years of space travel. Consequently, it is a medical requirement at NASA Johnson Space Center (JSC) that changes in bone mass be monitored in crew members by measuring bone mineral density (BMD) with dual-energy x-ray absorptiometry (DXA) before and after flight on astronauts who serve on long-duration missions (4-6 months). We evaluated this repository of medical data to track whether there is reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
106
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(118 citation statements)
references
References 14 publications
7
106
0
2
Order By: Relevance
“…However, once mechanical loads are reintroduced to skeletal extremities during reambulation, recovery of bone mass is often slow and incomplete. If full recovery is accomplished, it requires several times the duration of unloading [16][17][18]. During the initial phase of reambulation, bone mass may even continue to deteriorate in humans [16,19] and rodents [20], further compromising bone's structural integrity at a time when mechanical support is critical to withstand reloading of the skeleton.…”
mentioning
confidence: 99%
“…However, once mechanical loads are reintroduced to skeletal extremities during reambulation, recovery of bone mass is often slow and incomplete. If full recovery is accomplished, it requires several times the duration of unloading [16][17][18]. During the initial phase of reambulation, bone mass may even continue to deteriorate in humans [16,19] and rodents [20], further compromising bone's structural integrity at a time when mechanical support is critical to withstand reloading of the skeleton.…”
mentioning
confidence: 99%
“…Human bone loss during spaceflight is up to 2% bone mass per month with exposure to a space microgravity environment [1,2]. Bone-forming osteoblasts are vital factors in mechanosensing and mechanotransduction in vivo, and the biological responses of osteoblasts in altered gravity provide basic understanding of human bone loss in space.…”
mentioning
confidence: 99%
“…The derivation of a "half-life" index provided a time point (days after landing) which represented the timing of 50% restoration of BMD with Table 3 summarizes the "half-lives" and the losses at the time of landing for the skeletal sites evaluated for recovery. In spite of the large variability in the BMD measurements, and the uncertainty in half-life values (generally 3-9 months dependent upon skeletal site), the asymptotic increase in BMD over the post-flight period was clearly apparent and provided the basis for substantial recovery at ~ 4 times the half-life [33].…”
Section: Response On Earth After Spaceflightmentioning
confidence: 99%
“…Recently, a novel method of analyzing areal BMD has been reported that characterizes postflight skeletal recovery [33]. BMD measurements have been accumulated over a post-flight period lasting as long as five years.…”
Section: Response On Earth After Spaceflightmentioning
confidence: 99%